PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN DAN INTELECTUAL CAPITAL TERHADAP KINERJA UKM DI KABUPATEN BANYUMAS - Rini Widianingsih; Irianing Suparlinah; Agus Sunarmo; Rasyid Mei Mustofa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
According to the Ministry of MSME since 2017, in terms of the number of MSME units in Indonesia, they have a share of around 99.99 percent (62.9 million units) of the total number of business actors absorbing the national workforce. The purpose of this study is to identify the effect of financial literacy, financial inclusion and intellectual capital on the performance of SMEs in Banyumas Regency after the Covid Pandemic. This research method uses a survey with the method of data analysis using multiple regression analysis. The population in this study are small and medium enterprises that are still running after the Covid 19 pandemic disaster. The sample is taken with the criteria that the UKM is engaged in retail trade/stores in the Banyumas Regency area. The results of this study show that financial literacy, financial inclusion and intellectual capital have a positive impact on the performance of SMEs in Banyumas Regency, so that until now around 98 percent of SMEs are still surviving after experiencing the Covid 19 pandemic crisis since 2019.